2018
DOI: 10.1096/fj.201800956r
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 (P‐glycoprotein) regulates vitamin D absorption and contributes to its transintestinal efflux

Abstract: Efficient intestinal absorption of dietary vitamin D is required in most people to ensure an adequate status. Thus, we investigated the involvement of ATP binding cassette subfamily B member 1 (ABCB1) in vitamin D intestinal efflux. Both cholecalciferol (D) and 25-hydroxycholecalciferol [25(OH)D] apical effluxes were decreased by chemical inhibition of ABCB1 in Caco-2 cells and increased by ABCB1 overexpression in Griptites or Madin-Darby canine kidney type II cells. Mice deficient for the 2 murine ABCB1s enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 44 publications
3
27
0
Order By: Relevance
“…Vitamin D from dietary origin is absorbed in the intestine with about 70% efficacy in normal subjects. Although this process was for a long time considered to be a passive transport of a lipophilic molecule to access the lipid layer of the intestinal cells (82), more recent data suggest that vitamin D absorption and secretion from and into the lumen of the gut is medicated by carrier proteins that are also involved in cholesterol transport in the intestine (83). To what extent vitamin D esters are first digested and then absorbed or lost in the feces is still a point of discussion [see Solanum malacoxylon being a 1,25(OH) 2 D-glucuronide causing severe generalized calcinosis in grazing cattle in Argentina (84,85)].…”
Section: Functions Of Dbp (Table 2)mentioning
confidence: 99%
“…Vitamin D from dietary origin is absorbed in the intestine with about 70% efficacy in normal subjects. Although this process was for a long time considered to be a passive transport of a lipophilic molecule to access the lipid layer of the intestinal cells (82), more recent data suggest that vitamin D absorption and secretion from and into the lumen of the gut is medicated by carrier proteins that are also involved in cholesterol transport in the intestine (83). To what extent vitamin D esters are first digested and then absorbed or lost in the feces is still a point of discussion [see Solanum malacoxylon being a 1,25(OH) 2 D-glucuronide causing severe generalized calcinosis in grazing cattle in Argentina (84,85)].…”
Section: Functions Of Dbp (Table 2)mentioning
confidence: 99%
“…Besides SR-BI, ABCB1 (ATP binding cassette B1, also known as P-glycoprotein) and ABCG transporters, such as ABCG5, appear as good candidates. Indeed, a recent study combining in silico, cell culture, animal, and genetic approaches showed that ABCB1 was involved in vitamin D intestinal efflux [51]. Additionally, polymorphisms in the ABCG5 gene tended to contribute to individual response to lutein supplementation in humans [52].…”
Section: Carotenoid Absorption Through the Enterocytementioning
confidence: 99%
“…ABCB1 encodes for the P-glycoprotein, an ATP-dependent drug efflux pump for xenobiotics with broad substrate specificity, highly expressed in enterocytes. The association of P-glycoprotein with postprandial lycopene concentrations suggests that it could participate in the efflux of lycopene back to the intestinal lumen, as was recently shown for vitamin D [61]. ELOVL2 encodes for ELOVL fatty acid elongase 2 which catalyzes the elongation of eicosapentaenoic acid to docosapentaenoic acid and docosapentaenoic acid to docosahexaenoic acid.…”
Section: Genetic Variations Associated With Lycopene Bioavailabilitymentioning
confidence: 85%